A scale development study on the attitudes and behaviors of the society towards individuals using addictive substances - Şaşman Kaylı, Derya; Yılmaz, Gözde; İyilikçi, Osman (Journal of Dependence, 2020)
Objective: The aim of this study is to develop a scale to determine the attitudes and behaviors of the society towards individuals using addictive substancesMethod: The first stage sample of the study was composed of 396 people reached in eight districts determined randomly in the city center of Manisa. In the second stage of the study, test-retest stage sample was consisted of 66 undergraduate students of Manisa Celal Bayar University Faculty of Health Sciences and Faculty of Arts and Sciences. Demographic Information Form and Questionnaire on Attitudes and Behaviors toward Individuals Using Addictive Substance were used as data collection tool. Results: The scale has a single factor structure. The scale’s Kaiser-Meyer-Olkin (KMO) value was .92. Normed Fit Index (NFI) and Comparative Fit Index (CFI) were .91 and .93 respectively. Cronbach Alpha coefficient was .92 which indicates strong internal consistency.Conclusion: ''Attitude and Behaviors Scale for Individuals Using Addictive Substance'' has been evaluated as a valid and reliable scale in determining the attitudes of the society towards addiction.
Keywords: Drug abuse; attitude; validity; reliability